Effect of nationwide reimbursement of real-time continuous glucose monitoring on HbA1c, hypoglycemia and quality of life in a pediatric type 1 diabetes population: The RESCUE-pediatrics study - De Ridder, Francesca; Charleer, Sara; Jacobs, Seppe; Bolsens, Nancy; Ledeganck, Kristien J.; Van Aken, Sara; Vanbesien, Jesse; Gies, Inge; Casteels, Kristina; Massa, Guy; Lysy, Philippe A.; Logghe, Karl; et al. (Frontiers in Pediatrics, 2022)
Objective: Real-time continuous glucose monitoring (RT-CGM) can improve metabolic control and quality of life (QoL), but long-term real-world data in children with type 1 diabetes (T1D) are scarce. Over a period of 24months, we assessed the impact of RT-CGM reimbursement on glycemic control and QoL in children/adolescents with T1D treated with insulin pumps. Research Design & Methods: We conducted a multicenter prospective observational study. Primary endpoint was the change in HbA1c. Secondary endpoints included change in time in hypoglycemia, QoL, hospitalizations for hypoglycemia and/or ketoacidosis and absenteeism (school for children, work for parents). Results: Between December 2014 and February 2019, 75 children/adolescents were followed for 12 (n=62) and 24months (n=50). Baseline HbA1c was 7.2±0.7% (55±8mmol/mol) compared to 7.1±0.8% (54±9mmol/mol) at 24months (p=1.0). Participants with a baseline HbA1c≥7.5% (n=27, mean 8.0±0.3%; 64±3mmol/mol) showed an improvement at 4months (7.6±0.7%; 60±8mmol/mol; p=0.009) and at 8months (7.5±0.6%; 58±7mmol/mol; p=0.006), but not anymore thereafter (endpoint 24months: 7.7±0.9%; 61±10mmol/mol; p=0.2). Time in hypoglycemia did not change over time. QoL for parents and children remained stable. Need for assistance by ambulance due to hypoglycemia reduced from 8 to zero times per 100 patient-years (p=0.02) and work absenteeism for parents decreased from 411 to 214 days per 100 patient-years (p=0.03), after 24months. Conclusions: RT-CGM in pump-treated children/adolescents with T1D showed a temporary improvement in HbA1c in participants with a baseline HbA1c≥7.5%, without increasing time in hypoglycemia. QoL was not affected. Importantly, RT-CGM reduced the need for assistance by ambulance due to hypoglycemia and reduced work absenteeism for parents after 24months.